Theatre Ethnography and a Prism of Difference: A Dialogical Approach to Practitioner- Oriented Research - Rajendran, Charlene (SARE: Southeast Asian Review of English, 2017)
Researching theatre practice entails engaging critically with a sensuous medium that is complex and multi-layered, replete with intersections and integrations of thinking, feeling and doing, The experiential, transient and non-replicable nature of theatre for both performer and audience, raises questions for the researcher about what is knowable about theatre practice, how this can be known and ho what is known needs to be presented. As theatre practitioner and researcher I have been prodded to rethink how written analysis and interpretation of theatre pratice can be extended to included styles of representation and reflection that incorporate the dynamics of theatre as a medium which draws on a dialogical experience of theatre as well.